DESIGN AND DEVELOPMENT OF COCONUT PALM (Cocos nucifera L.) ROOF SHINGLES - A.R. Floresca; F.R. Siriban; A.P. Gesmundo (International Coconut Community Journal, 1989)
Tapered roof shingles from coconut wood were fabricated and treated separately with four preservatives, namely: copper‑chromearsenate, pentachlorophenol, copper sulfate and copper sulfate + potassium dichromate. Untreated and treated shingles were installed side in roof framed structures and exposed outdoor in the FPRDI "graveyard" area for weather and durability tests. Fabrication, treatment and installation costs of shingles were evaluated. Performance ratings on the different degradations such as splitting/checking and twisting of shingles, retention of original colour/appearance, and protection from weathering and fungal infection in relation to thickness, nailing patterns and treatments of coconut wood roof shingles after 11 months of weather exposure tests were evaluated and statistically analysed. Cost comparison between coconut wood roof shingles and G.I. corrugated sheet gauge #26 are also presented in this report.